Motion fairing - Jehee Lee; Sung Yong Shin (Proceedings Computer Animation '96, 1996)
Motion capturing is widely used for generating realistic motions. A 3D input device captures a sequence of 6 DOF rigid motion samples. The sampled data consists of two components, translation and orientation; the former is represented by a vector in R/sup 3/ and the latter by a rotation matrix in the rotation group, SO(3). Since the sequence of data contains sampling noises, the captured motion is now smooth and wiggles along the moving path. There are well-known fairing algorithms in Euclidean space based on difference geometry. Extending these for the motion data, we present a new fairing algorithm. The new algorithm iteratively minimizes the energy function reflecting the forces and torques, exerted on a moving object, to perform motion fairing.